SIMULASI SISTEM PELAYANAN BONGKAR MUAT KAPAL UNTUK MENGURANGI WAITING TIME MENGGUNAKAN SOFTWARE ARENA - David Hizkia Wardana; Herlina Herlina (LPPM Universitas Bina Bangsa, 2023)
PT Pelindo (Persero) branch of Tanjung Perak, the Jamrud Terminal division is a subsidiary of BUMN PT Pelabuhan Indonesia (Persero). This company has the duty to regulate and manage port business entities in the field of multipurpose terminal operations in Indonesia. In the process of loading and unloading services, problems are found, namely the length of the loading and unloading process which causes long waiting times. Ships waiting in line to get loading and unloading services can wait a maximum of about 138 hours, which can then get services for the loading and unloading process. There were long queues from 15 October to 21 October with 9-13 ships waiting to be served. The purpose of this research is to find out the average length of ship service time and to reduce ship waiting time. The intended target or scope is the North Jamrud and West Jamrud terminal divisions which are used for international loading and unloading. The method used to solve this problem is a discrete simulation method using the Arena software. Number out results were obtained from the Arena software simulation in the initial scenario of 39 ships. Several repair scenarios were carried out and the best repair scenario was obtained, namely the 3rd repair by adding 3 servers and obtaining a number out of 40 ships